2012
DOI: 10.1016/j.bbrc.2011.12.098
|View full text |Cite
|
Sign up to set email alerts
|

PrPC displays an essential protective role from oxidative stress in an astrocyte cell line derived from PrPC knockout mice

Abstract: The PrP(C) protein, which is especially present in the cellular membrane of nervous system cells, has been extensively studied for its controversial antioxidant activity. In this study, we elucidated the free radical scavenger activity of purified murine PrP(C) in solution and its participation as a cell protector in astrocytes that were subjected to treatment with an oxidant. In vitro and using an EPR spin-trapping technique, we observed that PrP(C) decreased the oxidation of the DMPO trap in a Fenton reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 41 publications
2
21
1
Order By: Relevance
“…For example, basal levels of ROS and lipid peroxidation were lower in PrP C -transfected neuroblastoma and epithelial cell lines compared with untransfected controls (Rachidi et al, 2003; Zeng et al, 2003). Moreover, PrP C expression by primary neurons, astrocytes and cell lines has been associated with lower levels of damage following exposure to various oxidative toxins (Brown et al, 1997b, 2002; Anantharam et al, 2008; Dupiereux et al, 2008; Bertuchi et al, 2012). A possible mechanism is that PrP C modulates the activities of the antioxidant enzymes that convert ROS into less toxic products—several studies have shown lower superoxide dismutase and glutathione peroxidase activities in the absence of PrP C expression (Brown et al, 1997b; Miele et al, 2002; Rachidi et al, 2003; Sakudo et al, 2003; Paterson et al, 2008).…”
Section: Prpc Functionmentioning
confidence: 99%
“…For example, basal levels of ROS and lipid peroxidation were lower in PrP C -transfected neuroblastoma and epithelial cell lines compared with untransfected controls (Rachidi et al, 2003; Zeng et al, 2003). Moreover, PrP C expression by primary neurons, astrocytes and cell lines has been associated with lower levels of damage following exposure to various oxidative toxins (Brown et al, 1997b, 2002; Anantharam et al, 2008; Dupiereux et al, 2008; Bertuchi et al, 2012). A possible mechanism is that PrP C modulates the activities of the antioxidant enzymes that convert ROS into less toxic products—several studies have shown lower superoxide dismutase and glutathione peroxidase activities in the absence of PrP C expression (Brown et al, 1997b; Miele et al, 2002; Rachidi et al, 2003; Sakudo et al, 2003; Paterson et al, 2008).…”
Section: Prpc Functionmentioning
confidence: 99%
“…Moreover, astrocytic PrP c expression appears to be important for reduction of hydrogen peroxide toxicity (Bertuchi et al, 2012), a reactive oxygen species whose production in mammalian cells is stimulated by hypoxia (Moller, 2001). …”
Section: Prpc-mediated Neuroprotection Against Hypoxiamentioning
confidence: 99%
“…PrP c acted as a radical scavenger in both ROS-rich solution and astrocytes cultures in vitro, and its activity was essential in their protection against oxidative stress. This feature may reflect its protective functions in conditions similar to those observed during neurodegeneration and ischemia [5]. Another defensive mechanism is associated with the ability of PrP c to bind co-chaperon molecule, called stress-inducible protein 1 (STI1).…”
Section: Prion Proteinmentioning
confidence: 99%